Optimization of Electrode Configuration for 3-D Brain EIT - Siyuan Bai; Yitong Guo; Weichen Li; Lei Wang; Xuetao Shi (IEEE Open Journal of Instrumentation and Measurement)
3-D brain electrical impedance tomography (EIT) holds great promise for real-time noninvasive imaging of various brain injuries. However, a reference method for selecting high-performance electrode configurations has not been proposed. In this article, the optimization of electrode layout, stimulation and measurement protocols, and the number of electrodes are sequentially performed. The signal quality and image reconstruction performance of simulated perturbations in four cortical regions are evaluated with various levels of noise taken into consideration. The results showed that, considering cost and convenience, the best number of electrodes is 20, which should be placed in the suboccipital and central vertex regions as needed. Electrodes with large spacing at different heights are mainly the driving electrodes, and the potential is collected in the appropriate adjacent channels. These principles are expected to provide general guidance for the electrode configuration methods of 3-D brain EIT in clinical applications.